Dissociation of equimolar mixtures of aqueous carboxylic acids in ionic liquids: role of specific interactions - Shukla, Shashi Kant; Kumar, Anil (Journal of Physical Chemistry B, 2015)
Hammett acidity function observes the effect of protonation/deprotonation on the optical density/absorbance of spectrophotometric indicator. In this work, the Hammett acidity, H-0, of equirriolar mixtures of aqueous HCOQH, CH3COOH, and CH3CH2COOH was measured in 1-methylimidazolium-, 1-methylpyrrolidinium-, and 1-methylpiperidinium-based protic ionic liquids (PILs) and 1-buty1-3-methylimidazolium-based aprotic ionic liquid (AIL), with formate (HCOO-) anion. Higher H-0 values were observed for the equimolar mixtures of aqueous carboxylic acids in protic ionic liquids compared with those of the aprotic ionic liquid because of the involvement of the stronger specific interactions between the conjugate acid of ionic liquid and conjugate base of carboxylic acids as suggested by the hard soft acid base (HSAB) theory. The different Ho values for the equimolar mixtures of aqueous carboxylic acids in protic and aprotic ionic liquids were noted to depend on the activation energy of proton transfer (E-a,H(+)). The higher activation energy of proton transfer was obtained in AIL indicating lower ability to form specific interactions with solute than that of PILs. Thermodynamic parameters determined by the ``indicator overlapping method'' further confirmed the involvement of the secondary interactions in the dissociation of carboxylic acids. On the basis of the thermodynamic parameter values, the potential of different ionic liquids in the dissociation of carboxylic acids was observed to depend on the hydrogen bond donor acidity (alpha) and hydrogen bond acceptor basicity (beta), characteristics of specific interactions.